Increased Growth Factors Play a Role in Wound Healing Promoted by Noninvasive Oxygen-Ozone Therapy in Diabetic Patients with Foot Ulcers. (24th June 2014) - Zhang, Jing; Guan, Meiping; Xie, Cuihua; Luo, Xiangrong; Zhang, Qian; Xue, Yaoming
Abstract : Management of diabetic foot ulcers (DFUs) is a great challenge for clinicians. Although the oxygen-ozone treatment improves the diabetic outcome, there are few clinical trials to verify the efficacy and illuminate the underlying mechanisms of oxygen-ozone treatment on DFUs. In the present study, a total of 50 type 2 diabetic patients complicated with DFUs, Wagner stage 2 4, were randomized into control group treated by standard therapy only and ozone group treated by standard therapy plus oxygen-ozone treatment. The therapeutic effects were graded into 4 levels from grade 0 (no change) to grade 3 (wound healing). The wound sizes were measured at baseline and day 20, respectively. Tissue biopsies were performed at baseline and day 11. The expressions of vascular endothelial growth factor (VEGF), transforming growth factor- β (TGF- β ), and platelet-derived growth factor (PDGF) proteins in the pathologic specimens were determined by immunohistochemical examinations. The effective rate of ozone group was significantly higher than that of control group (92% versus 64%, P < 0.05 ). The wound size reduction was significantly more in ozone group than in control group (P < 0.001 ). After treatment, the expressions of VEGF, TGF- β, and PDGF proteins at day 11 were significantly higher in ozone group than in control group. Ozone therapy promotes the wound healing of DFUs via potential induction of VEGF, TGF- β, and PDGF at early stage of the treatment. (Clinical trial registry number is ChiCTR-TRC-14004415 ).